The dilemma of land expansion and governance in rural China: A comparative study based on three townships in Zhejiang Province. (February 2018) - Yu, Zhenning; Wu, Cifang; Tan, Yongzhong; Zhang, Xiaobin
Abstract: Why do Chinese farmers continually utilize high-quality yet scarce cultivated land and extensively construct residences? Why is the Chinese government unable to control the continuous expansion of rural residential land after implementing strict economical and intensive land policies? To answer these questions, we launched a comparative study of three townships in Zhejiang Province. Based on a survey of 576 households and 72 rural government officials, this paper identified the determinants of rural house-building, explored different models of government intervention and provided recommendations for future government efforts. Results showed that (1) children, environment, investment, "mianzi", and "feng shui" factors were the main driving forces that influence farmers to construct residential structures, although primary and secondary differences in the various townships existed; (2) three problems in the specific governance emerged: the lack of farmers' unified action, failure to protect the rights of farmers, and the problem of meeting the funds demand of homestead replacement; (3) Actively exploring effective village planning, establishing linkages among stakeholders, effectively promoting farmers' participation, creating a service-oriented government, and introducing a Public-Private Partnership mechanism may effectively address the problems related to rural residential expansion and governance. The results indicated a need to pay more attention to the motivations of rural house-building, the interests of stakeholders and the funding arrangements of the project in future government intervention.